Antibiotic resistance pattern of isolated bacterial from salads - Adebayo EA; ON, Majolagbe; IO, Ola; MA, Ogundiran (Journal of Research in Biology, 2012)
The antibiotic resistance pattern of bacterial isolates from salad samples sold in a re-known food industry in different parts of Nigeria was investigated. A total of twenty-five bacterial isolates of six genera were encountered in the following proportion: Pseudomonas spp. (36%), Bacillus spp. (24%); Escherichia coli (16%), Proteus spp. (12%), Enterobacter spp. (8%) and Aeromonas hydrophila (4%). The antibiotic resistance pattern of the isolates revealed that resistance to eleven of the twelve antibiotic tested were above 50%. Streptomycin (44%) was the only antibiotic with resistance rate below this range. Resistance to Augmentin was the highest (96%), followed by Cotrimoxazole (92%) and Nitrofurantoin (88%). The results suggest the need for intensive surveillance of isolates throughout salad production continuum to prevent food-borne infections and also to detect emerging antimicrobial resistance phenotypes.